2019
DOI: 10.1101/640193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rectal cancer model establishes a platform to study individual responses to chemoradiation

Abstract: Rectal cancer (RC) is a challenging disease to treat that requires chemotherapy, radiation, and surgery to optimize outcomes for individual patients. No accurate model of RC exists to answer fundamental research questions relevant to individual patients. We established a biorepository of 32 patient-derived RC organoid cultures (tumoroids) from patients with primary, metastatic, or recurrent disease. RC tumoroids retained molecular features of the tumors from which they were derived, and their ex vivo responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The elucidation of the mechanisms underlying radioresistance in rectal cancer has been hampered by a lack of well-characterized pre-clinical model systems, including the low availability of in vitro cell lines of rectal cancer origin. Consequently, most pre-clinical research in the area of rectal cancer is conducted using colon cancer cell lines [ 9 , 10 ]. However, research has demonstrated that not only are right-sided colon cancers and left-sided CRCs anatomically distinct diseases, but also that there are different molecular, immunological and therapeutic implications between these two anatomically distinct sites [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elucidation of the mechanisms underlying radioresistance in rectal cancer has been hampered by a lack of well-characterized pre-clinical model systems, including the low availability of in vitro cell lines of rectal cancer origin. Consequently, most pre-clinical research in the area of rectal cancer is conducted using colon cancer cell lines [ 9 , 10 ]. However, research has demonstrated that not only are right-sided colon cancers and left-sided CRCs anatomically distinct diseases, but also that there are different molecular, immunological and therapeutic implications between these two anatomically distinct sites [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms contributing to radioresistance in rectal cancer are poorly understood [ 8 ]. Furthermore, research investigating mechanisms of radioresistance in rectal cancer is limited by the poor availability of characterized in vitro models of rectal cancer, with most research utilizing models of colonic origin [ 9 , 10 ]. Importantly, as colon and rectal cancers are demonstrated to be distinct diseases, and as radiation therapy is a common treatment in the management of rectal cancer but not colon cancer [ 11 , 12 , 13 , 14 ], the identification and characterization of in vitro models of radioresistant rectal cancer are crucial to elucidate the mechanisms of radioresistance in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the small dimensions of the organoids employed, and the fact that this set up does not reflect systemic distribution. Nevertheless, besides our study focused on targeted PDT, organoids are gaining increasingly more attention as realistic representations of tumors that enable effective drug screens, with a variety of drugs [21,42,43,44,45,46,47,48,49,50,51,52].…”
Section: Discussionmentioning
confidence: 99%